RITUAL ASPECTS OF ARISTOPHANES' BIRDS. - Straus, Michael (Acta Classica, 2018)
This article expands on recent scholarly attention to the ritual aspects of Athenian Old Comedy, including its possibly cultic and civic functions within the performative setting of the Great Dionysia, and proposes the use of linguistic and other tools as a means of providing deeper appreciation of such aspects of the plays. The article argues the point by applying these tools to a study of the use and occurrence of hymnic, sacrificial and wedding language and themes in Aristophanes' Birds, and by examining the interplay of the stage action with the festival's surrounding ritual and civic events.